Current and future landscape of poly (ADP-ribose) polymerase inhibition resistance. Issue 1 (February 2021) - Hinchcliff, Emily; Chelariu-Raicu, Anca; Westin, Shannon N.
Abstract : Purpose of review: To highlight relevant strategies to overcome poly(ADP-ribose) polymerase (PARP) inhibitor resistance and present key clinical trials. Recent findings: The use of PARP inhibition (PARPi) for frontline maintenance offers substantial clinical benefit in patients with homologous recombination-deficient tumors. However, expanding PARPi from recurrent therapy to frontline maintenance may potentially result in more PARPi resistant tumors earlier in the treatment continuum and data for the use of PARPi after PARPi remain limited. Clinical evidence demonstrates tumors may develop resistance to PARPi through demethylation of the BRCA promoter or BRCA reversion mutations. Multiple clinical trials investigating therapeutic strategies to overcome resistance, such as combinations of PARPi with antiangiogenic drugs, PI3K/AKT/mTOR, or MEK inhibitors have already been reported and more are ongoing. Furthermore, increasing the amount of DNA damage in the tumor using chemotherapy or cell cycle inhibitors such as ATM, ATR/CHK1/WEE1 is also under exploration. Summary: There is increasing clinical interest to identify options to enhance PARPi efficacy and overcome adaptive resistance. PARPi represent a class of drugs that have significantly impacted the treatment and maintenance of ovarian cancer; as the use of PARPi increases, better understanding of resistance mechanisms is essential.